Thermoregulation in a saxicolous population of the lizard Urosaurus ornatus from the northern Chihuahuan Desert, Mexico - Gadsden-Esparza, Héctor; Gatica Colima, Ana Bertha; Lara-Reséndiz, Rafael A.; Minjarrez-Flores, Nallely F.; Smith R., Geoffrey (2020)
Environmental temperatures often regulate the activity and physiological processes of ectotherms. Because environmental temperatures can vary significantly among seasons, lizards exposed to different thermal conditions in different months could differ in how they thermoregulate or behave. Here, we present a combination of field, laboratory, and modeling approaches to examine thermoregulation, habitat thermal quality, and hours of thermal restriction on activity in a saxicolous population of Urosaurus ornatus in two thermally contrasting months (June and October) in a micro-insular mountain system in the northern Chihuahuan Desert in Mexico. Both active and preferred body temperatures did not vary between months. In this population, U. ornatus is an active thermoregulator with highly accurate and efficient thermoregulation despite the thermal quality in both months. However, during the breeding season (June) activity is restricted (i.e., high number of hours of restriction) compared to the non-breeding season (October). Therefore, our results suggest that this saxicolous population of U. ornatus could be threatened by global climate change and it is essential to determine a conservation strategy for this population.